HUBUNGAN DUKUNGAN KELUARGA DENGAN LAMA PERSALINAN DI RUANG BERSALIN RUMAH SAKIT AURA SYIFA KABUPATEN KEDIRI - Triatmi Andri Yanuarini; Lupita Nur Afifah; Shinta Kristianti (Akademi Keperawatan Dharma Husada Kediri, 2019)
The period of childbirth is one of the indicators in the public health. The Maternal Mortality Rate in Indonesia is still high. One of the causes the high maternal mortality rate is due to the duration of labor. Fear, pain, and anxiety during the labor can interfere with psychological responses that may affect the progress of labor and possibly weaken the strength of mothers. It also causes stress, which leads to the adrenaline expulsion, resulting in narrowing of the blood vessels and reducing the blood flow that carries oxygen to the uterus, so it makes a decrease of uterine contractions that will lead to prolonged delivery time. The attention to psychological problems including involving family participation may affect the labor duration. The aims of this study was to determine the relationship between family support and the duration of labor in maternity mothers in Maternity Room Aura Syifa Hospital Kediri Regency.This research was analytic survey with is cross-sectional research. The population of this study was all maternity mothers in Maternity Room at Aura Syifa Hospital Kediri Regency. 21 Samples were taken and selected by using consecutive sampling technique.Data analysis technique used in this study is Fisher Exact test. The result of the calculation from Fisher Exact test is p = 1> 0,05.H1 is not accepted and H0 is acceptedso it can be concluded that the hypothesis in this study is rejected, in which there is no relationship between family support and the duration of labor.